1976
DOI: 10.1002/ajh.2830010208
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cells in culture

Abstract: Most laboratories using cells cultured in vitro maintain multiple cell lines. Such lines should be monitored for species and intraspecies characteristics to prevent invalidation of research work due to incidents of cell line cross-contamination. This report describes the results obtained when 246 cell cultures were examined for evidence of cross-contamination or mislabeling. Using species-specific antigens, isoenzyme electrophoresis, and chromosomes as markers of identity, 14% of the cultures submitted were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Using species specific antigens, isoenzyme electrophoresis, and chromosome analysis, he reported a frequency of 14% for interspecies contamination and 25% for intraspecies contamination. He concluded that, overall, 30% of the cell lines examined were incorrectly designated (Stulberg et al, 1976). At that time, a term "allozyme genetic signatures" was introduced by O'Brien.…”
Section: Prior Experience With Cell Cross-contamination: Evolution Ofmentioning
confidence: 97%
“…Using species specific antigens, isoenzyme electrophoresis, and chromosome analysis, he reported a frequency of 14% for interspecies contamination and 25% for intraspecies contamination. He concluded that, overall, 30% of the cell lines examined were incorrectly designated (Stulberg et al, 1976). At that time, a term "allozyme genetic signatures" was introduced by O'Brien.…”
Section: Prior Experience With Cell Cross-contamination: Evolution Ofmentioning
confidence: 97%
“…Several methods had been established to monitor cell culture identity using immunological markers (Stulberg et al 1976;O'Toole et al 1983), isoenzyme analysis (Halton et al 1983;Steube et al 1995) and karyologic examination (Miller et al 1971;NelsonRees et al 1974). The development of DNA-fingerprinting techniques offered detection of individual human samples (Jeffreys et al 1985;Stacey et al 1992) and is now used as an international standard for authentication of human cell lines Masters et al 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Several methods had been established to monitor cell culture identity using immunological marker (Stulberg et al 1976;O'Toole et al 1983), isoenzyme analysis (Halton et al 1983;Steube et al 1995) and karyological examination (Miller et al 1971;Nelson-Rees et al 1974). Speciesspecific antibodies are also available commercially and these have been used to confirm species of origin by indirect fluorescence or immunoperoxidase staining (Hay 2002).…”
Section: Introductionmentioning
confidence: 99%